Handbook of antioxidants : bond dissociation energies, rate constants, activation energies, and enthalpies of reactions /: bond dissociation energies, rate constants, activation energies, and enthalpies of reactions. (2019) - Denisov, E. T (Evgeniĭ Timofeevich)
No abstract available